Role of Forests in Environment - Murthy, T. Krishna (Indian Forester, 1999)
Forest is a major component of the whole ecosystem. The only remedy to set our whole edifice i.e. environment right in a proper way is to bring back all our degraded forests to full stocking and afforest all waste lands.